KEBIJAKAN MELEGALISASI CRYPTOCURRENCY SEBAGAI UPAYA PEMERINTAH JEPANG MENGAMANKAN KEAMANAN NASIONAL JEPANG - Safitri, Eulisa; Putranti, Ika Riswanti (Journal of International Relations, 2019)
This paper aims to understand Japan’s policy regarding cryptocurrency. In 2016, Japan decided to legalize cryptocurrency and become the first country to do so in the world. Japan's decision to legalize the cryptocurrency became interesting and needs to be questioned. Because, even though cryptocurrency bring many advantages, but these advantages also make states worried about the implications of the usage of cryptocurrency in crime. Meanwhile, other countries like Indonesia, Thailand, Kyrgizstan, Bangladesh, Ecuador, Rusia has decided to prohibit cryptocurrency transaction and did not recognize cryptocurrency as a currency. To understand why Japan became the first country to legalize cryptocurrency, the concept of National Security will be used in this paper.  By using National Security concept, it will be explained that without regulation to regulate cryptocurrency, cryptocurrency will become a threat to Japan’s cyber security and economic security, and in the end it will become a threat to Japan’s national security.